Forward engagement RSIS as a think tank of international studies and security in the Asia-Pacific - Chong, Alan (World Scientific, 2017)
This was how RSIS' mission began under the stewardship of the late President S.R. Nathan. RSIS began (as IDSS) in 1996 as a form of policymakers' clairvoyant on security matters. To date, it is Singapore's 'frontline' think tank on Asia-Pacific security, counter-terrorism, inter-religious dialogue and non-traditional security threats.